Investigating The Use of Teaching Strategies to Promote English as a Foreign Language Students’ Cognitive Engagement Case of First Year LMD Students at the Department of English, Mohamed-Cherif Messaadia University, Souk Ahras - ARAMI, Nesrine (My University, 2023)
ABSTRACT This study aims to investigate the effectiveness of using teaching strategies on enhancing learners’ cognitive engagement at the Department of the English Language at Mohamed Cherif Messaadia University, in Souk-Ahras. Teatching strategies are designed to engage students, promote critical thinking, and create an effective learning environment. Therefore, this exploratory, descriptive research utilized a qualitative study to collect data with two main research instruments. Initially, an in-depth semi-structured interview was conducted with six (06) EFL teachers selected conveniently. Secondly, a non-participant observation was conducted during the second semester (2023) with group one (01) of first year English students over six sessions during “ Initiation to Linguistics ” , "Corrective and Articulatory Phonetics " and "Techniques of University "classes, with two sessions per module. The results indicated that the participants agreed upon the efficiency of teaching strategies in English learning. In addition, it was proved that teaching strategies impact positively students’ cognitive engagement, critical thinking, analytical thinking and creativity. Based on these results, the raised hypotheses were confirmed. ------------- الملخص تهدف هذه الدراسة إلى التحقيق في فعالية استخدام استراتيجيات التدريس في تعزيز المشاركة المعرفية للمتعلمين في قسم اللغة الإنجليزية في جامعة محمد الشريف مساعدية سوق أهراس. تم تصميم استراتيجيات التدريس لإشراك الطلاب ، وتعزيز التفكير النقدي ، وخلق بيئة تعليمية فعالة. استخدم هذا البحث الاستكشافي الوصفي دراسة نوعية لجمع البيانات. وقد استخدمت أداتان رئيسيتان. في البداية ، تم إجراء مقابلة متعمقة شبه منظمة مع ستة (06) من معلمي اللغة الإنجليزية كلغة أجنبية تم اختيارهم بشكل ملائم. ثانيا ، تم إجراء ملاحظة غير مشارك خلال الفصل الدراسي الثاني (2023) مع المجموعة الأولى (01) من طلاب اللغة الإنجليزية في السنة الأولى على مدى ست جلسات خلال دورات; بدء اللغويات; التصحيحية والمفصلية وتقنيات الجامعة; ، جلستين لكل وحدة. وأشارت النتائج إلى أن المشاركين اتفقوا على كفاءة استراتيجيات التدريس في تعلم اللغة الإنجليزية . بالإضافة إلى ذلك ، ثبت أن استراتيجيات التدريس تؤثر بشكل إيجابي على مشاركة الطلاب المعرفية والتفكير النقدي والتفكير التحليلي والإبداع . بناء على هذه النتائج ، تم تأكيد الفرضيات المطروحة. --------------- Résumé Cette étude vise à étudier l'efficacité de l'utilisation de stratégies d'enseignement sur l'amélioration de l'engagement cognitif des apprenants dans le Département de langue anglaise de l'Université Mohamed Cherif Messaadia, à Souk-Ahras. Les stratégies d’enseignement sont conçues pour engager les élèves, promouvoir la pensée critique et créer un environnement d'apprentissage efficace. Cette recherche exploratoire et descriptive a utilisé une étude qualitative pour recueillir des données. Deux instruments principaux avaient été utilisés. D’abord, un entretien approfondi semi-structuré a été mené avec six (06) enseignants EFL sélectionnés de manière pratique. Ensuite, une observation non participante a été menée au second semestre (2023) auprès du groupe un (01) d'étudiants anglais de première année sur six sessions lors des cours “ Initiation à la Linguistique ” , "Correctif et Articulatoire" et "Techniques de l'Université", deux sessions par module. Les résultats ont indiqué que les participants étaient d'accord sur l'efficacité des stratégies d'enseignement dans l'apprentissage de l'anglais. De plus, il a été prouvé que les stratégies d'enseignement ont un impact positif sur l'engagement cognitif, la pensée critique, la pensée analytique et la créativité des élèves. Sur la base de ces résultats, les hypothèses soulevées ont été confirmées.